ANALISIS SIFAT KIMIA DAN KARAKTERISTIK SENSORI YOGHURT NABATI BERBASIS SARI HANJELI (Coix lacryma-jobi) - Mimah Mutmainah; Riandani, Andini Putri; Hasibuan, Anggi Khairina Hanum (Pasundan Food Technology Journal (PFTJ), 2025)
The development of plant-based yogurt is necessary as an alternative for individuals with lactose intolerance and cow’s milk allergies. Cereals, legumes, and nuts can serve as raw materials for producing plant-based yogurt. This study aims to evaluate the nutritional content and sensory characteristics of yogurt made from Coix lacryma-jobi (hanjeli) milk as a locally sourced fermented product alternative. The research employed an experimental method using a completely randomized design with a single factor: the ratio of hanjeli milk added at levels of 50%, 60%, and 70%. Proximate analyses were conducted, including moisture, ash, protein, fat, and carbohydrate content, alongside sensory evaluations (taste, aroma, texture, color, appearance, and overall acceptance). The optimal formula was determined using the Exponential Comparison Method. The selected yogurt formula (F1), with a 50% hanjeli milk ratio, had the following characteristics: moisture (83.36%), ash (0.69%), protein (3.09%), fat (2.21%), carbohydrate (10.65%), taste score (4.30), aroma (4.97), texture (5.00), color (5.67), appearance (5.63), and overall acceptance (4.50). Keyword: plant-based yogurt, hanjeli milk, nutritional content, sensory evaluation